The different role of separated liquid and solid fraction in THP sludge anaerobic digestion - Teo, Beng Ngee (2018)
Wastewater treatment process uses biological-reaction in the removal of organics contaminants. This process will create sludge, that contains mainly microbes, solid and water content. Further treatment is required to remove the microbes and contaminants in the sludge, one known process is the anaerobic digestion. Anaerobic digestion is widely adopted and proven process, however hydrolysis as the rate limiting steps has limited its applications. Sludge with prior treatment is introduced to reduce the time needed for hydrolysis and thereby enhance the performance of the anaerobic digestor. Thermal hydrolysis pretreatment (THP) is one widely used pretreatment that utilize high temperature to break down hard cell wall of the microbes to release intracellular and extracellular substances. In this study, the liquid and solid fractions of THP sludge were further separately fed into anaerobic digester. The methane production performance from these two fractions was investigated. The maximum methane production (262.8± 2.1 ml CH4/g tCODadd) was obtained with the digestion of liquid fraction which was increased by 160.7% compared to the samples that were fed with raw sludge with the absence of pre-treatment. Digestion of liquid fraction also showed the highest volatile solid (VS) reduction (83.0%) which was followed by the digestion of THP sludge raw sludge and solids phase successively. The study concluded that the rate limiting factors for THP sludge digestion were more associated with the solid fraction During digestion the dewaterability of sludge samples was improved, which was mainly associated with the significant consumption of soluble organic substances like proteins and polysaccharides in the liquid phase.